2014
DOI: 10.3109/09638288.2014.935493
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic view of comorbid depression and generalized anxiety disorder symptom change in chronic heart failure: the discrete effects of cognitive behavioral therapy, exercise, and psychotropic medication

Abstract: The findings support the use of multifaceted interventions in the rehabilitation of HF patients with comorbid psychiatric needs. Implications for Rehabilitation Comorbid depression and anxiety disorders are a clinical and research focus that deserves more attention in the treatment of heart failure patients. Cognitive behavioral therapy, exercise, and anxiolytic use was associated with significant changes in depression and anxiety though discrete effects were evident. Multifaceted interventions are most likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 68 publications
0
37
1
Order By: Relevance
“…Recently it was shown that collaborative care programs were effective for a reduction in generalized anxiety and depression symptoms [ 72 , 73 ]. Moreover, exercise, anxiolytic use and cognitive behavioral therapy for GAD were associated with a reduction in somatic depressive symptoms among persons with comorbid depression disorder-GAD and heart failure [ 74 ]. In the population undergoing CABG surgery, prior interventions have indicated small to medium treatment effect sizes regarding reduction in depression and anxiety symptoms [ 75 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that collaborative care programs were effective for a reduction in generalized anxiety and depression symptoms [ 72 , 73 ]. Moreover, exercise, anxiolytic use and cognitive behavioral therapy for GAD were associated with a reduction in somatic depressive symptoms among persons with comorbid depression disorder-GAD and heart failure [ 74 ]. In the population undergoing CABG surgery, prior interventions have indicated small to medium treatment effect sizes regarding reduction in depression and anxiety symptoms [ 75 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac Failure Review, 2, 110-112. Tully, P. J., Selkow, T., Bengel, J., & Rafanelli, C. (2015). A dynamic view of comorbid depression and generalized anxiety disorder symptom change in chronic heart failure: the discrete effects of cognitive behavioral therapy, exercise, and psychotropic medication.…”
Section: Key Practice Pointsmentioning
confidence: 99%
“…These clients may frequently be considered 'complex'. Tully et al (2015) found that co-morbid anxiety and depression in people with heart failure could be treated with GAD-focused CBT, within a collaborative care approach, leading to improvements in both depression and anxiety. They stressed the importance of patient preference in treatment modality and the benefits of graded exposure to exercise.…”
Section: Introductionmentioning
confidence: 99%
“…8 In a report, cognitive decline was associated with higher depression, 9 and in another study, depression and anxiety were closely linked and multifaceted interventions that included cognitive behavioral therapy, exercise, and anxiolytics were used to meet psychiatric needs. 10 In the Self-Management and Care of Heart Failure (SMAC-HF) intervention, mental health clinical nurse specialists were part of the shared appointments team and depression evaluations were completed, but cognitive decline was not studied and nurse practitioners and the other multidisciplinary providers did not alter the clinical treatment plan to alter depression. Moreover, research results of the benefits of depression assessment, cognitive behavioral therapy, and medication management to treat depression in patients with HF is limited, 11,12 reflecting a need for novel interventions.…”
Section: Article See P 888mentioning
confidence: 99%